Study of Brain Computer Aided Diagnostic System Based on CT Image - Zhang, Guo Yun; Guo, Long Yuan; Yuan, Shuai; Wu, Jian Hui (Applied Mechanics and Materials, 2014)
Brain computer aided diagnostic system based on CT image has been widely applied for medical clinical field, which studies image preprocessing, feature extraction and image classification diagnosis based on digital image processing technology. This paper presents system design and realization of aided diagnostic technology for brain CT image. The dynamic grey level range of CT image is extended by adopting segmental linear stretching method at first. Then textural features of CT image are extracted based on GLCM (grey level concurrence matrix). BP neural network algorithm is used to design a classifier for textural features vector of CT image at last, which identifies normal and abnormal brain CT image. Test result shows that the method presented has good accuracy, quick speed and strong robustness for realtime application.